Model based on γ-glutamyltransferase and alkaline phosphatase for hepatocellular carcinoma prognosis - Xu, Xin-Sen (Baishideng Publishing Group Inc, 2014)
AIM: To determine the prognostic value of alkaline phosphatase (ALP) and γ-glutamyltransferase (GGT) for hepatocellular carcinoma (HCC) . METHODS: We analyzed the outcome of 172 HCC patients who underwent liver resection. Receiver operating characteristic (ROC) curve analysis was performed to determine the cut-off value of ALP and GGT. Then, preoperative risk factors for survival were evaluated by multivariate analysis. Based on the significant factors, a prognostic score model was established. RESULTS: By ROC curve analysis, ALP > 120 U/L and GGT > 115 U/L were considered elevated. Overall survival (OS) and tumor-free survival (TFS) for patients with elevated ALP and GGT were significantly worse than for patients with ALP and GGT within the normal range. Multivariate analysis showed that the elevated levels of ALP, GGT and tumor size were independent prognostic factors. Giving each positive factor as a score of 1, we established a preoperative prognostic score model. The 5-year OS for patients with a score of 0, 1, 2 and 3 were 84.0%, 45.9%, 44.1% and 0%, respectively, while the TFS was 80.6%, 40.0%, 38.8% and 0%, respectively. When combining patients with scores of 1 and 2 into the middle risk group, and patients with scores of 0 and 3 into the low-risk and high-risk groups, respectively, different outcomes would be significantly distinguished by the risk groups. CONCLUSION: Elevated ALP and GGT levels were risk predictors in HCC patients. Our prognostic model might vary the outcomes of patients from different risk groups.